Processed multichannel seismic data, including SCREECH Transact 1, crossing the Newfoundland margin, acquired during the R/V Maurice Ewing survey EW0007 2000) (IEDA: Marine-Geo Digital Library, 2019)
This data set consists of SCREECH Transect 1 (1MCS) and lines 101, 102, and 103. This ODP site survey on the Newfoundland margin was a joint project, SCREECH (Studies of Continental Rifting and Extension on the Eastern Canadian SHelf), between the University of Wyoming, WHOI, Dalhousie University, and Danish Lithosphere Centre scientists. The Ewing acquired MCS, magnetic, gravity, and multibeam bathymetric data while the Oceanus acquired wide-angle reflection/refraction data via ocean-bottom seismometers/hydrophones (OBS/Hs). This cruise was to provide a critical dataset for testing models of continental rifting, breakup, and initiation of seafloor spreading in a non-volcanic rifted environment. Its objectives were to: 1) characterize the nature of the crust transitional between oceanic and continental crust in the region; 2) provide a comparison with the Iberian margin, thereby allowing testing of models of pure-shear vs. simple-shear during rifting; and 3) determine the amount of igneous material intruded and extruded during rifting, providing comparative data with other volcanic rifted margins, such as the East Greenland margin. Funding was provided by NSF (grants OCE98-19599 and OCE98-19053), Dalhousie University, Geological Survey of Denmark and Greenland, Danish National Research Foundation (Danmarks Grundforskningsfond), and the Natural Sciences and Engineering Council of Canada.